Industrial Design of Yarn Speed Monitoring System in Positive Feed Circular Knitting Machine - Mohammad Ehsan Momeni Heravi (Tekstilec)
As constant yarn feeding tension is essential in the formation of uniform stitches, the lack of a monitoring system in a circular weft knitting machine capable of measuring the uniformity of the yarn feeding speed in different driven belts and comparing the feeding rate during the knitting process has led to the use of experimental methods which are dependent on skilled operators. Additionally, in the case of any defects, the equalisation is done by the operator using the trial-and-error method, which consequently increases the risk of human error. Considering the importance of a uniform adjustment of yarn feeding speed on the quality of final fabrics, a monitoring system for measuring and reporting yarn feeding speed was designed. Following its installation on a circular weft knitting machine, the performance of the system in an industrial environment was evaluated. A comparison with the traditional system proved the functionality of the designed automation process. The current study highlights the characteristics of an appropriate sensor, the applicable installation place and direct data reception without intermediaries.